2005
DOI: 10.1302/0301-620x.87b10.16536
|View full text |Cite
|
Sign up to set email alerts
|

The insertion geometry of the posterolateral corner of the knee

Abstract: We have quantitatively documented the insertion geometry of the main stabilising structures of the posterolateral corner of the knee in 34 human cadavers. The lateral collateral ligament inserted posterior (4.6 mm, sd 2) and proximal (1.3 mm, sd 3.6) to the lateral epicondyle of the femur and posterior (8.1 mm, sd 3.2) to the anterior point of the head of the fibula. On the femur, the popliteus tendon inserted distally (11 mm, sd 0.8) and either anterior or posterior (mean 0.84 mm anterior, sd 4) to the latera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
76
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 25 publications
4
76
1
1
Order By: Relevance
“…Watanabe et al (1993) and Yang et al (2011) found that the distance from the center of the attachment of PT to the lateral epicondyle of the femur was 10.32 ± 3.2 mm and 11.32 ± 1.2 mm, respectively. Considering that attachment of the LCL was located near the lateral epicondyle (LaPrade et al 2003;Brinkman et al 2005), the distance found in this study between the attachment of PT and LCL in the different types shown in Table 3 and Fig. 2, is similar to the results of Watanabe et al (1993) and Yang et al (2011).…”
Section: The Popliteus Tendon and Its Clinical Implicationssupporting
confidence: 79%
See 2 more Smart Citations
“…Watanabe et al (1993) and Yang et al (2011) found that the distance from the center of the attachment of PT to the lateral epicondyle of the femur was 10.32 ± 3.2 mm and 11.32 ± 1.2 mm, respectively. Considering that attachment of the LCL was located near the lateral epicondyle (LaPrade et al 2003;Brinkman et al 2005), the distance found in this study between the attachment of PT and LCL in the different types shown in Table 3 and Fig. 2, is similar to the results of Watanabe et al (1993) and Yang et al (2011).…”
Section: The Popliteus Tendon and Its Clinical Implicationssupporting
confidence: 79%
“…However, Jung et al (2010) classified the locations of PT attachment with respect to the LCL attachment into three types: posteroinferior, just inferior, and double attachment by bifurcate bundles. Brinkman et al (2005) and Jung et al (2010) reported that the attachment of PT was posterior to LCL in 94.1% (2/34) and 72% (13/18) samples. The classification in our present study was similar to that reported by Jung et al (2010) except for type I, which was found instead of bifurcate bundles, and we found that type II and type III accounted for 75.3% (61/81) of the knees examined.…”
Section: The Popliteus Tendon and Its Clinical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The attachment sites of LCL and PT on femoral condyle in the literature markedly varied. It was stated that PT attached 0.84-18.5 mm anterior to the LCL (Bartonícek, 2005;Brinkman et al;Kim et al). In some other studies, PT has been expressed to locate in three positions: posteroinferior, just inferior or posterior to the LCL in extension position of the knee (Ullrich et al, 2002;Zhang et al;Jung et al).…”
Section: Lateral (Fibular) Collateral Ligamentmentioning
confidence: 98%
“…Injuries of PLC are surgically important as playing major role against varus rotation, external rotation and posterior tibial translation (LaPrade et al, 2003;Brinkman et al, 2005;Espregueira-Mendes & da Silva, 2006& James et al, 2015. Among the numerous lateral structures of the knee, the lateral (fibular) collateral ligament (LCL), popliteus tendon (PT) and popliteofibular ligament (PF) are the key structures for posterolateral stability (LaPrade et al).…”
Section: Introductionmentioning
confidence: 99%